Leadership Transformation Culture in Private Higher Education Institutions in Balikpapan - Pangemanan, Cindy Olivia; Asriandi (Yayasan Sinergi Kawula Muda, 2025)
This study examines leadership culture transformation in Balikpapan's private higher education institutions (PHEIs) facing modern challenges. Qualitative multi-site methods, data was collected through interviews and observations from various stakeholders. Results show PHEIs confronting diverse challenges: quality improvement, resource limitations, and governance issues. Transformation requires a holistic approach including consistent leadership, capacity development, and organizational restructuring. While positive impacts like increased collaboration and efficiency have emerged, obstacles such as role ambiguity and limited autonomy persist. Continuous evaluation is crucial for long-term success in improving PHEI performance and quality. Inspirational leadership is key to successful change. The study highlights complex challenges faced by PHEIs and emphasizes comprehensive strategies for effective transformation. Despite positive outcomes, ongoing assessment is needed to address remaining barriers and ensure sustained improvement in Balikpapan's private higher education sector.